Towards a model for student selection in clinical psychology. (3rd September 2013) - Schweitzer, Robert; Khawaja, Nigar; Strodl, Esben; Lodge, Jason; Coyne, Joe; King, Robert
Abstract Background Selection of candidates for clinical psychology programmes is arguably the most important decision made in determining the clinical psychology workforce. However, there are few models to inform the development of selection tools to support selection procedures. The study, using a factor analytic structure, has operationalised the model predicting applicants' capabilities. Method Eighty‐eight clinical applicants for entry into a postgraduate clinical psychology programme were assessed on a series of tasks measuring eight capabilities: guided reflection, communication skills, ethical decision making, writing, conceptual reasoning, empathy, and awareness of mind and self‐observation. Results Factor analysis revealed three capabilities: labelled "awareness" accounting for 35.71% of variance; "reflection" accounting for 20.56%; and "reasoning" accounting for 18.24% of variance. Fourth year grade point average (GPA) did not correlate with performance on any of the selection capabilities other than a weak correlation with performance on the ethics capability. Conclusions Eight selection capabilities are identified for the selection of candidates independent of GPA. While the model is tentative, it is hoped that the findings will stimulate the development and validation of assessment procedures with good predictive validity which will benefit the training of clinical psychologists and, ultimately, effective service delivery.